Gold‐Hydrogen Nanoclusters: Atom‐Precise Model to Unveil Catalytic Mechanism and Growth Process of Gold Nanoparticles. Issue 6 (16th April 2020) - Wang, Zhao‐Yang; Zang, Shuang‐Quan
Abstract : Gold nanoclusters show high catalytic performance in various chemical reactions including the hydrogenation and hydrogen evolution reactions. Hydrogen involved gold clusters is the ideal model to investigate the hydrogen‐gold cluster interactions, the influence of H atoms on the electronic structures of the gold clusters, the particle growth process, and the catalytic mechanism. This paper highlights the pioneering experimental and theoretical works in the gold‐hydrogen cluster studies, and overviews the existing challenges. Abstract :